2013
DOI: 10.1136/annrheumdis-2013-203403
|View full text |Cite
|
Sign up to set email alerts
|

The outcome and cost-effectiveness of nurse-led care in people with rheumatoid arthritis: a multicentre randomised controlled trial

Abstract: ObjectiveTo determine the clinical effectiveness and cost-effectiveness of nurse-led care (NLC) for people with rheumatoid arthritis (RA).MethodsIn a multicentre pragmatic randomised controlled trial, the assessment of clinical effects followed a non-inferiority design, while patient satisfaction and cost assessments followed a superiority design. Participants were 181 adults with RA randomly assigned to either NLC or rheumatologist-led care (RLC), both arms carrying out their normal practice. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(181 citation statements)
references
References 48 publications
6
166
1
8
Order By: Relevance
“…Despite wide-scale adoption, evidence of the effectiveness of nurse specialists and their clinics is limited. Recent work has addressed this gap with two recent multi-centre studies undertaken in the UK of effectiveness and economic value [3] and, in France, of co-A c c e p t e d M a n u s c r i p t morbidity management [4]. Results provide robust evidence to support nurse-led clinics in the management of Rheumatoid Arthritis and co-morbidity detection with nurse-led clinics having higher 'general satisfaction' than physician-led clinics [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite wide-scale adoption, evidence of the effectiveness of nurse specialists and their clinics is limited. Recent work has addressed this gap with two recent multi-centre studies undertaken in the UK of effectiveness and economic value [3] and, in France, of co-A c c e p t e d M a n u s c r i p t morbidity management [4]. Results provide robust evidence to support nurse-led clinics in the management of Rheumatoid Arthritis and co-morbidity detection with nurse-led clinics having higher 'general satisfaction' than physician-led clinics [5].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in parallel with the RCT of outcome and cost effectiveness for RA patients attending nurse-led Rheumatology clinics: a nationwide multi-centre study conducted in the UK [3]. Whilst the trial assessed whether there were any difference in outcomes of patients attending nurse-led clinics or physician-led clinics, the current study examined processes of care, focussing on the interactional style observed within consultations.…”
Section: Methodsmentioning
confidence: 99%
“…RA is a chronic inflammatory arthritis that affects nearly 1.5 million adults in the United States 1 and 2 million in Europe. 2 It was traditionally a debilitating disease, but with advances in treatment, RA is now a manageable chronic disease state. The predominant feature of RA is synovial inflammation manifested as swelling and tenderness of small, medium, and large joints in a symmetric pattern, with a predilection for the smaller joints of the hands and feet.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de, tradicionalmente, as pessoas com AR serem monitorizadas periodicamente em consultas médicas (Primdahl et al, 2014;Sorensen et al, 2015), vários estudos e a síntese narrativa evidenciam resultados favoráveis quando este seguimento é realizado também por enfermeiros, nomeadamente na capacidade funcional, na qualidade de vida, na dor (Ndosi et al, 2014), e na satisfação global (Koksvik et al, 2013;Ndosi et al, 2014;Primdahl et al, 2014). Para além destes resultados é ainda evidente a não-inferioridade (não existindo diferenças estatisticamente significativas) das CE em relação às CR, por exemplo, nos outcomes: atividade da doença, capacidade funcional (Larsson et al, 2014;Primdahl et al, 2014;Sorensen et al, 2015), fadiga (Koksvik et al, 2013;Primdahl et al, 2014), qualidade de vida (Koksvik et al, 2013;Primdahl et al, 2014;Sorensen et al, 2015) e dor (Koksvik et al, 2013;Larsson et al, 2014;Primdahl et al, 2014).…”
Section: Interpretação Dos Resultadosunclassified
“…Resultados desfavoráveis são reportados apenas para o outcome capacidade funcional, no grupo das CE (Watts et al, 2015) e para o outcome fadiga (Ndosi et al, 2014 …”
Section: Interpretação Dos Resultadosunclassified